Extending the Semiotics of Embodied Interaction to Blended Spaces - O’Neill, Shaleph; Benyon, David (Human Technology, 2015)
In this paper, we develop a new way of understanding interactions in blended spaces. We do this by developing ideas about embodied semiotics and then apply these ideas to the analysis of interaction in mixed-reality blended spaces (where the physical world and digital world are blended deliberately to provide new forms of interaction). We discuss how blended spaces provide a new medium within which people have experiences. The semiotic analysis reveals how blended spaces are constructed across the physical and the digital, highlighting the ontology, topology, volatility, and agency present within them. It shows how people move between the physical and digital spaces through the objects and places that anchor them together. Our approach reveals more about the way bodily and higher cognitive functions are brought into play within a holistic interactive experience in which people move physically and conceptually through the layers of experience that make up the interaction.